Peningkatan Keseimbangan Tubuh Lansia Melalui Senam di Sebuah Balai Pelayanan dan Penyantunan Lansia - Riyeni Dwita Andria; Agung Riyadi; Sariman Pardosi (JURNAL KEPERAWATAN RAFLESIA, 2020)
The aging process experienced by every human being in the form of physical and psychological changes. Physical changes cause a decrease in the body's ability to maintain balance. Impaired body balance increases the risk of falls and injury to the elderly. Regular exercise can reduce impaired body balance. A good sport for the elderly is gymnastics. The purpose of this study was to determine the effect of gymnastic exercise on the level of balance of the body of the elderly in the Balai service and elderly elderly sponsors. This study uses a Pre-experimental method with one group pretest-posttest design method. A sample of 26 people was obtained with non-probability sampling techniques and purposive sampling techniques. The elderly balance research instruments were collected using a questionnaire and observation sheet. Statistical test using Wilcoxon signed ranks test found that there was an influence of elderly exercise on the level of balance of the elderly body in the service and sponsorship of the elderly in Bengkulu City with a value of p = 0.001 (p <α 5%). Based on the above results it is advisable for the elderly to do gymnastics elderly regularly to prevent disturbance of balance..